Understanding the impact of clinical and leadership development activities for pediatric cardiac nurses in India - Magdeline Aagard; Adriana Dobrzycka; Bistra Zheleva; Veeralakshmi Rajasekhar; Shubhitha Menon; Vaisakh Gopakumar (Wolters Kluwer Medknow Publications, 2023)
The major challenges for pediatric cardiac nursing in India include inadequacies in their levels of education and lack of recognition of their vital role in the health-care system. The aim of this study was to understand the impact of the leadership educational initiatives on pediatric cardiac nursing taken by Children's HeartLink and the Pediatric Cardiac Society of India. Semi-structured interviews were conducted with eight pediatric cardiac nurse leaders from different Indian hospitals. A review of interviews from a previous study and an extensive literature review provided further foundational data on two major themes. The first theme on nursing education focused on nursing curriculum update, continuing education, and leadership development. The second theme focused on improving the value of nursing in public perception, value in hospitals, and their career promotions. The study identified the potential targets for improvement and provided a nursing career development ladder applicable to India.